OPTIMATION RESERVATION HOTEL DURING PANDEMIC COVID -19 WITH ECOMMERCE ARCHITECTURE - Hidayat, Muhammad Taofik; Fauzan, Raden Arya Rafi; Pambudhi, Muhamad Rilo; Raja, M. Arda; Rahmatdiansyah, Andie; , Sukenda (CENTRAL ASIA AND THE CAUCASUS, 2022)
The function of a reservation is to sell goods and services in the field of online tourism, in times that have started to improve some tourist attractions have opened and offer a superior product through social media or using print media, a promotional strategy currently relying on help website-based information technology that functions as a promotional medium, facility information and processing hotel room reservations, another important thing is the establishment of good relations between customers and the hotel so that there is transparency starting from prices and facilities as well as discounts and special prices, with the implementation of this reservation system proven that the hotel owner can carry out a management and manage the room booking process as well as hotel promotion media that can still continue even during the pandemic.